Continuance Intention Analysis Using Unified Theory Of Acceptance And Use Of Technology Model And Unfavorable Attitude Toward Cash Payment Variable In The Case Study Of Pt. Xyz Bank M-Banking Application - Faqih, Muhammad; Djunita Pasaribu, Rina; Wahyuningtyas , Ratri (International Journal of Science, Technology & Management, 2025)
The mobile banking application of PT. XYZ offers two main services, which are the core banking functions: collecting funds from the public and disbursing funds to the public. However, a decline in the number of users of the XYZ mobile banking app has been observed in both Monthly Active Users and Monthly Transacting Users. The study involves respondents who represent the target market of Bank XYZ, such as active users and users who make transactions on the XYZ mobile banking application. Thus, the objective of this research is to evaluate the IT functional-level strategy of PT. XYZ's mobile banking application concerning continuance intention. Further, the study aims to explain the relationships between the variables of performance expectancy, effort expectancy, social influence, and facilitating conditions from the UTAUT model, as well as the variable of unfavorable attitude toward cash payment (UATC), in relation to satisfaction and continuance intention, and the interaction between these variables. Employing a quantitative research method, the sampling technique was non-probability sampling, specifically purposive sampling, as the population was already sufficiently specific to mobile banking users of PT. XYZ, with 310 respondents who are users of PT. XYZ's mobile banking application. Data analysis was performed using CB-SEM with a Maximum Likelihood approach. The research findings indicate that performance expectancy has the most significant influence on continuance intention. The results also show that satisfaction, as an intervening variable, strengthens the significant effect of performance expectancy, effort expectancy, and social influence. Based on the findings, it is recommended to focus on performance expectancy, in line with the results of the descriptive analysis, which suggest that it is an area requiring urgent and critical evaluation. Enhancing performance expectancy can help sustain continuance intention among Monthly Active Users and Monthly Transacting Users of the XYZ mobile banking application.